2019
DOI: 10.1111/and.13367
|View full text |Cite
|
Sign up to set email alerts
|

The c.‐190 C>A transversion in promoter region of protamine 1 gene as a genetic risk factor in Egyptian men with idiopathic infertility

Abstract: Protamines are considered the most important structure in the sperm nucleus, and they are proteins with a significantly large amount of amino acids carrying a positive charge, which allows the formation of the tight package of the genomic DNA in the spermatozoa. Many authors studied the abnormalities in the protamine 1 (PRM1) and/or protamine 2 (PRM2) genes and reported their possible association with male infertility. The chromosome 16 (16p13.2) carries these genes containing multiple undiscovered single nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…So far, researchers have screened PRM1 gene polymorphisms in infertility patients from different countries and districts ( 75 - 77 ). Collecting these studies, we find some variations related to male infertility, including the c.-109G>C, c.102G>T and c.119G>A in oligozoospermic men ( 78 ), c.-191C>A in oligozoospermic and asthenozoospermic men ( 79 ), and 230C>A in teratozoospermic infertile men ( 77 ). However, a recently published meta-analysis by Nemati et al analyzed all the published articles about PRM1 and PRM2 polymorphisms, and evaluated the association with susceptibility to male infertility.…”
Section: Clinical Utilization Of Prm1mentioning
confidence: 99%
“…So far, researchers have screened PRM1 gene polymorphisms in infertility patients from different countries and districts ( 75 - 77 ). Collecting these studies, we find some variations related to male infertility, including the c.-109G>C, c.102G>T and c.119G>A in oligozoospermic men ( 78 ), c.-191C>A in oligozoospermic and asthenozoospermic men ( 79 ), and 230C>A in teratozoospermic infertile men ( 77 ). However, a recently published meta-analysis by Nemati et al analyzed all the published articles about PRM1 and PRM2 polymorphisms, and evaluated the association with susceptibility to male infertility.…”
Section: Clinical Utilization Of Prm1mentioning
confidence: 99%
“…They screened nine polymorphisms in both genes, and only three of them, 139C>A in PRM1 and 298G>C, higher frequency than the control group (Nabi et al, 2018). Also, investigation of the association of c.-191C>A polymorphism in the PRM1 gene with male infertility revealed that the CA and AA genotype were significantly correlated with low sperm concentration and reduced sperm motility (p = .001) (Abdallah et al, 2019). On the other hand, analysis of the PRM1 gene in infertile men with teratozoospermia showed the frequency of the CA genotype of 230C>A polymorphism was significantly higher in teratozoospermia men compared to control group with p = .001 (Dehghanpour et al, 2019).…”
Section: Ta B L Ementioning
confidence: 99%
“…It has shown that deficiency of protamine instigated a serious spermatogenesis disturbance, reduced sperm count, motility and morphology, thus causing male infertility (Akmal et al, 2016;Tüttelmann et al, 2018). Through the PRM1 gene variations studies, some variations were detected related to male infertility, including the c.-107G>C, c.102G>T and c.119G>A in oligozoospermic men (Ravel et al, 2007), c.-191C>A in oligozoospermic and asthenozoospermic men (Abdallah et al, 2019), and 230C>A in teratozoospermic infertile men (Dehghanpour et al, 2019). In the present study, the patients with approved OAT features were included, which is the most common cause of subfertility among men (Rahiminia et al, 2018), for the PRM1 gene mutation.…”
Section: Introductionmentioning
confidence: 99%